(untitled) (Third Sector Social Economic Review, 2025)
This study examines the determinants of corporate green transformation through a comparative analysis of 5,871 firms in 16 EU countries and 739 firms in Türkiye, using data from the 2018–2020 Business Environment and Enterprise Performance Survey (BEEPS) conducted by the EBRD, World Bank, and EIB. A Green Transformation Index, based on firm-level environmental practices, classifies firms above the median as green-transition achievers. Logistic regression models assess the role of six conceptual categories: (i) external pressures (customer requirements, climate-related losses, and pollution), (ii) regulatory exposure (energy taxes and performance standards), (iii) perceived obstacles (environmental regulations and tax rates), (iv) organizational capacity (strategic planning, board governance, certifications, multi-establishment status, and female ownership), (v) operational conditions (power outages, informal competition, and CO₂ emissions), and (vi) financial and market access (credit availability, export share, and stock listing). Findings reveal that customer requirements, energy performance standards, and formal strategic planning consistently drive green transformation, with stronger effects in Türkiye. In the EU, voluntary commitments, such as certifications, female ownership, and exposure to environmental risks, play a larger role. Access to finance facilitates transformation in both regions, while regulatory burden deters progress in Türkiye. Policy recommendations emphasize strengthening market-based incentives, applying regulations consistently, expanding green finance, enhancing governance, and mitigating operational vulnerabilities. These steps can shift sustainability from compliance to competitive advantage, improving environmental performance and long-term resilience.